Performance Index Model of Small Dam in Semi-Arid Area - Priseila Pentewati; Pitojo Tri Juwono; Lily M. Limantara; Moh. Sholichin (Salehan Institute of Higher Education, 2024)
The aim of this research is to build a model of small dam performance index in semi-arid areas by considering 4 aspects that are physical, institution, service, and operation and maintenance aspects. Research locations are 85 small dams that spread to 8 islands and 5 SWS in 22 regencies in Nusa Tenggara Timur Province. The data consists of secondary data from BWS NT II and primary data from survey results and survey blank filling to 85 locations of small dams in the field. The methodology consists of Structural Equation Modeling Partial Least Squares (SEM-PLS) and Generalized Reduced Gradient (GRG). The analysis result shows that physical; institution; service; and operation and maintenance aspects are significantly influenced by the performance index of small dams. The structural analysis expresses that physical; institution; service; and operation and maintenance aspects are positively and significantly influenced by the performance index of small dams. The novelty in this research is the performance index of small dams that is successfully developed and tested by using field data and GRG. In addition, this model gives accurate value to the performance index of small dams in semi-arid areas in Nusa Tenggara Timur Province. However, the performance index model of small dams in semi-arid areas is formulated as follows: IK physical = 0.093 KT + 0.128 KTE + 0.159 KBS + 0.087 BPL + 0.155 JD + 0.145 KBLY + 0.233 KBP; IK institution = 0.58 DOP + 0.42 RA; IK service = 0.56 KBL + 0.09 AM + 0.12 VG + 0.09 WK + 0.14 PA; IKOM = 0.360 PKOP + 0.515 PPE + 0.125 KSOP. The general formulation for performance index of small dams is I IDK-Pentewati = 0.15 IK physical + 0.12 IK institution + 0.20 IK service + 0.53 IK OM. Doi: 10.28991/CEJ-2024-010-08-014 Full Text: PDF